Metode Dakwah Ustadz Bahrun dalam Meningkatkan Semangat Ibadah Jama’ah di Desa Air Buluh Kecamatan Ipuh Kabupaten Mukomuko - Angela Gopindo; Muhamad Fajri (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Regency, since the arrival of Ustadz Bahrun. This change can be seen from the condition of the mosque and congregation before and after Ustadz Bahrun was appointed preacher in the village of Air Buluh. The mosque, which was previously empty of religious activities and activities, is now bustling with congregational activities, which are organized by Ustadz Bahrun such as daily, weekly, monthly, and even yearly studies. Jama'ah who used to be negligent and neglected the implementation of congregational prayers, now there are many congregational prayer activities at the mosque. The aim is to find out what da'wah methods are used by Ustadz Bahrun in increasing the spirit of congregational worship in Air Buluh Village, Ipuh District, Mukomuko Regency. The results of the research are Ustadz Bahrun's da'wah method in increasing the spirit of congregational worship consisting of three da'wah methods. The first is the method of da'wah al-hikmah where Ustadz Bahrun preaches gently, and provides an understanding of what is right and wrong, and Ustadz Bahrun can understand the conditions of men who differ socially, racially, ethnically and understand their religion, the second method of da'wah mauidzatul Hashanah It can be seen that Ustadz Bahrun was able to give advice inviting the congregation to return to the path blessed by Allah SWT. the third method of da'wah mug is billati hiya ahsan where ustadz Bahrun uses this method in terms of religious discussions so that congregations who do not know about a problem can be discussed directly with ustadz Bahrun so that the ustadz is able to provide solutions to these problems.